Platoniškoji nuosaikumo politika ir šiuolaikinė pilietinė teorija. - Bartninkas, Vilius (Problems / Problemos, 2023)
This paper examines Plato's later model of civic participation in relation to contemporary civic theories. It argues that, although the Platonic model satisfies such common criteria for civic theories as equality, autonomy, and empowerment, the key concept to understand this project is moderation. It is moderation that structures and unifies the constituent elements of this model (the rule of law, the persuasion of the preambles, the empowering economy and education). It also explains what kind of personal disposition is central to achieving a stable and rational political order.